A Thermo-Active Laccase Isoenzyme From Trametes trogii and Its Potential for Dye Decolorization at High Temperature - Yang, Xulei; Wu, Yuanyuan; Zhang, Yu; Yang, En; Qu, Yuan; Xu, Huini; Chen, Yuhui; Irbis, Chagan; Yan, Jinping (Frontiers in Microbiology, 2020)
A thermo-activation and thermostable laccase isoenzyme (Lac 37 II) produced by Trametes trogii S0301 at 37 C was purified to apparent homogeneity by anionic exchange chromatography and sephadex G-75 chromatography, with 12.3% of yeiled and a specific activity of 343.1 U·mg-1. The molecular weight of the purified Lac 37 II was estimated to be approximately 56 kDa in 12% sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE). The optimal pH and temperature for the protein was 2.7 and 60 °C, respectively. The purified Lac 37 II showed higher resistance to all tested metal ions and organic solvents except for Fe2+ and Cd2+ at 37 C and the activity of the purified Lac 37 was significantly enhanced by Cu2+ at 50 mM. The Kcat, Km and Kcat/Km of Lac 37 II were 2,977 s-1, 16.1 μM and 184.9 s-1 μM-1 respecively in the condition of pH 2.7 and 60 C using ABTS as a substrate. Peptide-mass fingerprinting analysis showed that the Lac 37 II matched to the gene-deduced sequences of lcc3 in T. trogii BAFC 463, other than Lcc1, Lcc 2 and Lcc 4. Compared with laccase prepared at 28 C, the onset of thermo-activation of Lac 37 II activity occurred at 30 C with an increase of 10%, and reached its maximum at the temperatures range of 40-60 C with an increase of about 40% of their original activity. Furthermore, Lac 37 II showed the efficient decolorization ability towards triphenylmethane dyes at 60 C, with decolorization rates of 100% and 99.1% for 25 mg·L-1 malachite and crystal violet in 5 h, respectively, when hydroxybenzotriazole was used as a mediator. In conclusion, it is the first time to report a thermo-activation laccase from a thermophilic Trametes trogii strain, which has a better enzyme property and higher decolorization ability among fungal laccases, and it also has a further application prospective in the field of biotechnology.